Extraction of Squalene From Tea Leaves (Camellia sinensis) and Its Variations With Leaf Maturity and Tea Cultivar - Sheng, Yue Yue; Xiang, Jing; Wang, Kai Rong; Li, Ze Yu; Li, Kai; Lu, Jian Liang; Ye, Jian Hui; Liang, Yue Rong; Zheng, Xin Qiang (Frontiers in Nutrition, 2022)
Squalene is a precursor of steroids with diverse bioactivities. Tea was previously found to contain squalene, but its variation between tea cultivars remains unknown. In this study, tea leaf squalene sample preparation was optimized and the squalene variation among 30 tea cultivars was investigated. It shows that squalene in the unsaponified tea leaf extracts was well separated on gas chromatography profile. Saponification led to a partial loss of squalene in tea leaf extract and so it is not an essential step for preparing squalene samples from tea leaves. The tea leaf squalene content increased with the maturity of tea leaf and the old leaves grown in the previous year had the highest level of squalene among the tested samples. The squalene levels in the old leaves of the 30 tested cultivars differentiated greatly, ranging from 0.289 to 3.682 mg/g, in which cultivar “Pingyun” had the highest level of squalene. The old tea leaves and pruned littering, which are not used in tea production, are an alternative source for natural squalene extraction.